The Analogy between Ordinary and Relative Preference Analysis - Clower, Robert W. (The Review of Economics and Statistics, 1953)
3.5 per cent of national income, while subtractions amount to only 0.4 per cent. (See p. I04.) 4. The so-called technical bias works both ways. It may result in some cases from greater detail of information for I937 than for I899the reason ascribed by Mr. Lebergott-but it results in many more cases simnply from greater diversification of products. High concentration is less indicative of monopoly for a product with many close substitutes than for one with few. In view of the vast proliferation of products and expansion of markets over the last half century, one may doubt the comparability of any specific measure of concentration as applied to both beginning and end of the period. As in the case of growth of output, no index can adequately reflect such qualitative factors. This is not to say that they should be overlooked. 5. The term slight is not used to describe the rise of 6 percentage points in the fraction of private income but the rise of i.9 percentage points in the fraction of national income. The former rise is characterized in my monograph as substantial, a fit counterpart for significant. (See p. 45.) Most of these issues are discussed in my monograph. I cannot agree with Mr. Lebergott that his criticisms fundamentally alter the picture of the growth of monopoly and concentration gathered from recent studies, such as those of Adelman, Stigler, and myself. Nevertheless, such criticisms are of inestimable importance in pointing out errors, no matter how minor they might seem; for the goal is to unearth facts, not to prove cases.